Challenges in the implementation of design-build infrastracture projects in the University of the Philippines System - Villalobos, Paul Dwayne T.; Germar, Fernando J. (Quezon City College of Engineering, University of the Philippines Diliman, 2015)
The design-build procurement method for infrastructure projects entails the engineering design and construction of a project to be accomplished by a single entity. This may speed up project delivery times. In the Philippine setting, there is a lack of research into design-build problems that may occur in local infrastructure projects. Thus, this study aims to look at challenges encountered in design-build infrastructure projects of the University of the Pllilippines (U.P.) System. Ultimately, this study aims to supply solutions to the problems based on industry feedback and review of related literature. Design-build infrastructure projects in the U.P . system were first profiled through inquiries of different U.P. offices. Surveys were then given to contractors and U.P. offices involved in the design-build process in order to identify occurring problems based on a list of problems compiled from related literature. Also, respondents assessed design-build projects they have participated in through project success criteria and project performance criteria. A total of 16 design-build projects were profiled including buildings, laboratories, road works, and canal works. In the survey, only a limited number of U.P. offices, and contractors participated. Respondents assessed the following projects: Philippine Genome Center, Design and Renovation of the U.P. Quezon Hall Building, and the Acacia Residence Hall and Law Centennial Dormitory. Top problems ranked according to the respondents' assessment are 'changes in design take a long time to be approved', 'Delays in conunencing work because under-estimated time needed to obta in government approvals and other related agencies' approval', and 'Clients' payment to progress billings are late'. Other problems noted by respondents included high cost of bidding for contractors, U.P. offices are overworked, and many changes in design during implementation. Solutions formulated include a two-step bidding process to encourage contractor participation, a creation of a dispute resolution board, hiring more U.P. staff, decreasing initial design done by the client. setting a deadline for all design revisions and additions, conducting pre-bidding site inspection, instilling clearer communication among all project participants, and imposing penalties. Red tape in the government and inefficient paper work must be combatted through constant follow-ups.
Thesis (B.S. Civil Engineering)--University of the Philippines Diliman
Keywords: University of the Philippines -- Buildings; Construction industry -- Management; Construction projects